UJI POTENSI ANTIBAKTERI EKSTRAK ETANOL DAUN KAYU METANG (Lunasia amara blanco) TERHADAP Staphylococcus aureus - Dasor, Aurelia Yuliarty Carmila; Sanam, Maxs U. E.; Ndaong, Nemay A. (FAKULTAS KEDOKTERAN HEWAN UNIVERSITAS NUSA CENDANA, 2021)
Staphylococcus aureus is a normal flora in living things found on the skin and mucous membranes. Staphylococcus aureus can potentially cause infections of the skin and mammary glands. Natural ingredients that have the potential as antibacterial are Kayu Metang Leaves (Lunasia amara blanco) Manggarai people use the leaves to treat diabetes and wounds on the skin. The purpose of this study was to determine the secondary metabolites contained in Kayu Metang leaves and to determine the level of effective concentration as an antibacterial Staphylococcus aureus. This study used four replications and there were three variations of the ethanol extract concentration, namely 5%, 10%, and 20%. Data analysis in this study employed One-Way Anova followed by normality test and homogeneity test with 95% confidence level (a = 0.05). The results revealed that the inhibition zones resulting from concentrations of 5%, 10%, and 20% had different diameter values ​​and had the same average antibacterial strength, namely the strong category because the range of inhibition zones formed from 9.525 mm to 14.65 mm. The result of the one-way Anova test was a significance of p = 0.397. There was no significant difference in each concentration of metang wood leaf extract with a p value> 0.05. The use of metang wood extract had a smaller inhibitory power than the use of the antibiotic ciprofloxacin, but the use of metang wood extract has been shown to inhibit S. aureus bacteria. This study concluded that the leaves of metang wood (Lunasia amara blanco) have been shown to contain alkaloids, flavonoids, saponins, steroids and triterpenoids, and antibacterial compounds to the growth of Staphylococcus aureus.